2015
DOI: 10.1111/cod.12392
|View full text |Cite
|
Sign up to set email alerts
|

Nickel hypersensitivity and orthodontic treatment: a systematic review and meta‐analysis

Abstract: SummaryNickel-containing alloys are widely used in orthodontic appliances, even though nickel is by far the most common contact allergen. However, the scientific evidence concerning allergic reactions to nickel in orthodontic patients has not been evaluated systematically. The objective of this study was to investigate whether the prevalence of nickel hypersensitivity is affected by orthodontic treatment. Unrestricted electronic and manual searches were performed until July 2013 for human clinical studies asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
0
26
1
Order By: Relevance
“…A recent meta-analysis reports an average prevalence of nickel hypersensitivity of 19% in orthodontic patients, 5 while our study found a somewhat lower prevalence. On the other hand, a low incidence of allergic reactions during orthodontic treatment is reported, ranging between 0.03% and 0.3%.…”
Section: Discussioncontrasting
confidence: 76%
“…A recent meta-analysis reports an average prevalence of nickel hypersensitivity of 19% in orthodontic patients, 5 while our study found a somewhat lower prevalence. On the other hand, a low incidence of allergic reactions during orthodontic treatment is reported, ranging between 0.03% and 0.3%.…”
Section: Discussioncontrasting
confidence: 76%
“…Even though Ni allergy is frequently observed during skin contact, allergic reactions in the oral cavity are rare [7,43]. In addition, there is evidence of a reduced prevalence of Ni hypersensitivity in patients having received orthodontic treatment before ear piercing [15,19]. Interestingly, new insights in pathomechanism of Ni hypersensitivity have revealed that a specific innate immune receptor (Toll-like receptor 4) is implicated in this event [42].…”
Section: Resultsmentioning
confidence: 99%
“…However, Ni is the main sensitizer for contact hypersensitivity and, therefore, often blamed for adverse reactions during orthodontic therapy. On the other side, a current meta-analysis indicated that orthodontic treatment may even reduce the incidence of Ni hypersensitivity, when the treatment preceded Ni sensitization through ear piercings [19]. Cases of Ni-induced allergic reaction during orthodontic therapy are rare and often related to extraoral appliances, as dermal Ni contact seems to be able to induce hypersensitivity more easily than the contact with oral mucosa.…”
Section: +2mentioning
confidence: 99%
“…The higher prevalence among women is explained with the often and closed contact with objects containing nickel and/or cobalt, especially with jewelries and/or piercing which women start to use since early in life (36). The wide spread of nickel sulphate in our everyday life (in sunglasses frame, door handles, spoons and forks in the kitchen, medical instruments, dental materials, metal chair and as well as ingredient in a lot of food products) explains the high prevalence of positive patch tests to this substance compared to other allergens less common in everyday life (37,38). Besides industrial materials (cement, mortar, plaster, bricks), potassium dichromate is also common in everyday life and can be found in leather clothing, shoes, colored gloves, matches and tattoos (24,34,38).…”
Section: Discussionmentioning
confidence: 99%